Lignocellulosic Biomass Pretreatment for Enhanced Bioenergy Recovery: Effect of Lignocelluloses Recalcitrance and Enhancement Strategies - Banu J, Rajesh; Sugitha, S; Kavitha, S; Kannah R, Yukesh; Merrylin, J; Kumar, Gopalakrishnan (Frontiers in Energy Research, 2021)
Bioenergy recovery from lignocellulosic (LC) biomass is the beneficial and sustainable approach due to its abundant availability. On the Otherhand, its recalcitrant nature makes the biomass to resist biological hydrolysis and it limits the conversion potential of organics to biomethane. Thus, it is essential to evaluate the association among the recalcitrant nature of LC biomass and its biomethane conversion efficiency. Consequently, this review critically recaps the recalcitrance of LC biomass and its effects on bioenergy recovery, its composition and characteristics. In addition, various enhancement approaches (pretreatments) were conferred as main aspect which plays main role in biomass disintegration and biomethane increment. Based on up -to -date information, elevated energy input and cost necessities of the pretreatments are the main factors that mediates the economic feasibility of the process. The present review apart from spotlighting the pretreatment efficiency, it also focusses on the challenges and limitations of enhancement strategies, energy and technoeconomic feasibility of the various pretreatments of LC biomass.